Isolation of 8-Hydroxy-6-Methoxy-2-Methyl Anthraquinone 3-O-β-D-Glocupyranoside from Raphanus sativus and its Anti-inflammatory Activity - Srinivas, K.; Prakash, K. (Asian Journal of Chemistry, 2010)
The isolation of 8-hydroxy-6-methoxy-2-methyl anthraquinone- 3-O-β-glucopyranoside from the leaves of Raphanus sativus which was confirmed by spectral data and chemical conversions. The anti-inflammatory activity of EtOH extract and isolated compound of Raphanus sativus was tested and the data showed a significant inhibition of carrageenan induced paw oedema in rats treated with alcoholic extract and isolated compound or Raphanus sativus. which is equivalent to that produced by phenylbutazone.